A Solution To Resolve In Realizing Quality Learning At Madrasah Diniyah Takmiliyah - Yugo, Tri (Tatar Pasundan: Jurnal Diklat Keagamaan, 2024)
This study aims to examine the obstacles to meeting learning standards at Madrasah Diniyah Takmiliyah (MDTA) in Baleendah District, Bandung Regency. The research method used is a qualitative approach with case studies. Data collection techniques are carried out through in-depth interviews, direct observation, and documentation. Five MDTA heads are the source of data, namely from MDT Zahratun Nisa, MDT Baitul 'Arif, MDT Ummul Fahmi, MDT Al Jihad, and MDT Husnul Khotimah. The results of the study show that the main obstacles faced include limited infrastructure, low competence of educators, and lack of support from parents and the community. The strategies used by individual principals vary, from seeking external support to improving teacher discipline and motivation. This study provides recommendations for improving teacher competence, collaboration with external parties, and increasing the participation of parents and the community in supporting the quality of learning at MDTA. With greater support from various parties, MDTA can significantly improve the quality of its learning. Keywords: Madrasah Diniyah Takmiliyah; learning standards; infrastructure, educator competence; parent participation